IMPLEMENTASI SISTEM DAN PROSEDUR PEMBERIAN KREDIT USAHA MANDIRI (KUM) PADA PT BANK SULSELBAR CABANG GOWA - marniati marniati; Asdi Asdi; Muhamaad Akib (Universitas Muhammadiyah Makassar, 2019)
This study aims to describe how the implementation of the system and procedures for providing independent business credit (KUM) at PT. Bank Sulselbar, Gowa Branch. The type of research used is descriptive qualitative research, which is a study that is intended to collect data and information about a phenomenon and facts about the object and the place of research in accordance with what was at the time of the research. This research was conducted at Jalan Hos Coakrominoto No. 2 Sungguminasa Gowa by selecting 3 resource persons, namely 2 employees in the division of Bank Sulselbar's credit division in Gowa branch and 1 person as a customer in providing independent business credit. Data collection techniques use observation or observation techniques, interviews and documentation. The system and procedure for granting loans used by the bank is based on the Standard Operating Procedure (SOP). The results of the study show that using standard operating procedures (SOPs) is able to facilitate the lending process so that it can run effectively